MENINGKATAN SOFT SKILL MAHASISWA MELALUI EDUPRENEURSHIP - Thayyibi, Muhammad Ilham; Subyantoro (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2022)
The materials or teaching materials taught at educational institutions are not in accordance with the needs of the industrial world so that it has an impact on graduates of educational institutions not being able to compete in the industrial world because of their lack of ability, namely the ability of soft skills which will determine one's success. So the purpose of this research is to explain the impact of eduprenesurship in improving students' soft skills. This study uses library research, namely by reviewing the literature related to the research theme. Edupreneurship has an impact on the 13 soft skills possessed by a person